Kajian Historis Tuan Ma sebagai Relikui di Larantuka dalam Perspektif Etnohistori - Mufti, Muhammad 'Afwan; Wahyudi, Deny Yudo; Wijaya, Daya Negri (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This article aims to examine the historical study of Tuan Ma as a reliquary in Larantuka from an ethnohistorical perspective. This study attempts to explain in detail the historicity of Tuan Ma from an ethnohistoric perspective, including Portuguese domination and power in Larantuka; Tuan Ma's role as a relic of the continuity of traditional beliefs and Catholicism in Larantuka; and the sacredness of Tuan Ma for the people of Larantuka. By using the ethnohistorical approach as a research method, it is expected to answer this research in the perspective of culture and history in Larantuka. This research shows that Tuan Ma is not just a religious symbol, but also a cultural heritage that represents a dialogue and synthesis between local traditions and global influences. The sacredness of Tuan Ma continues to live as an integral part of the identity of the Larantuka community, reflecting the sustainability and transformation of tradition in the face of changing times. This research is expected to be a stimulus for other studies on religious symbols and local traditions that can survive and thrive in the context of globalization and modernity.